Dreams - Jung, C. G. (Carl Gustav), 1875-1961 (Bollingen series, 2011)
Dream analysis is a distinctive and foundational part of analytical psychology, the school of psychology founded by C.G. Jung and his successors. This volume collects Jung's most insightful contributions to the study of dreams and their meaning. The essays in this volume, written by Jung between 1909 and 1945, reveal Jung's most essential views about dreaming--especially regarding the relationship between language and dream. Through these studies, Jung grew to understand that dreams are themselves a language, a language through which the soul communicates with the body. The essays included a.